Phamacognostical Evaluation and Antimicrobial Activity of Paeonia sinjiangensis K.Y. Pan in Xinjiang, China - Gong, H.Y.; Liu, J.W.; Wang, X.H.; Hu, L.Y.; Zhao, J.L.; Zhang, C. (Asian Journal of Chemistry, 2013)
This paper deals with the phamacognostical evaluation of the crude drug Paeonia sinjiangensis K.Y. Pan, which is a perennial herb belonging to the family Ranunculaceae and an important crude drug in Traditional Chinese Medicine. The microscopic, physico-chemical, preliminary physicochemical parameters were presented in this work may be to establish the authenticity of Paeonia sinjiangensis K.Y. Pan and can possibly help to differentiate the drug from its other species. Meanwhile, it was determined total phenols and tested for its antimicrobial activity in this study. The total phenols content of Paeonia sinjiangensis K.Y. Pan was 9.58 ± 1.03 mg QE/g dry wt. It showed strong inhibition against Blastomyces albicans and possessed considerable activity against Staphylococcus aureus and Escherichia coli.